Strategi Pemasaran Kreatif TikTok Shop UMKM - Yulianti, Yulianti; Purnamasari, Devi (Tuturlogi: Journal of Southeast Asian Communication, 2025)
Semarang, as the economic hub of Central Java, holds great potential with a total of 29,868 registered Micro, Small, and Medium Enterprises (UMKM). In the digital era, platforms like TikTok Shop offer significant marketing potential, yet UMKM in Semarang have not widely adopted it. This study aims to identify the creative TikTok Shop marketing strategies implemented by UMKM in Semarang and the factors that influence their success. In this study, the theory used is marketing communication Business to consumer theory and uses a qualitative approach with a case study method. The object of this research is the UMKM @dapoerrindu_semarang which has a TikTok Shop account in Semarang. Data collection were conducted through interviews, observation and documentation. The research findings show that UMKM @dapoerrindu_semarang have implemented several creative strategies such as ease of transactions, product qualifications, and service quality. There are several factors that cause the use of TikTok Shop among UMKM in Semarang to remain low, including the lack of adequate infrastructure support, HR skills, and understanding of digital creativity. Future research should explore consumer perspectives on TikTok Shop, particularly its impact on purchasing decisions and its effectiveness as a community-based e-commerce platform.